Methodologic and Theoretic Characteristics of the International Economic Relations in the Conditions of the Globalization - Dimova, Ruska (Research Papers, 2014)
The study treats the global characteristics of international economic relations. The new methodology is explained and implemented as a global approach. The global approach includes historical and logical approaches based on the theory of epochs and the theory of systems. The contribution of the international economic relations for a more complex and multicentric world economic system is also defined through the global approach. The defended thesis is that globalization changes completely the international economic relations which acquire new characteristics, exist through a new structural model and require a global explanation frame.